Interactive effects of developmental and adult nutrition on lifespan and fecundity in a genetically diverse Drosophila population - Andrew Jones; De’anne Donnell; Elizabeth G. King; Enoch Ng’oma (PLoS ONE, 2025)
Developmental conditions, including temperature, diet, and parasite exposure, can shape adult fitness phenotypes across species. While studies often examine the independent effects of early-life and adult conditions on life history traits, fewer have focused on their interactive effects, particularly in genetically diverse populations. Here, we investigate how larval and adult diet interact to influence lifespan and fecundity in a genetically diverse population of Drosophila melanogaster. We manipulated protein availability across larval and adult stages and found significant larval-adult diet interactions affecting both traits, though in different ways. Several key patterns emerged, including age- and sex-specific effects, survival differences in the post-median life phase, shifts in the timing of peak fecundity, and sustained egg production in older stages. Protein reduction increased male maximum lifespan and female lifetime fecundity, while lower adult protein intake delayed egg-laying by approximately two weeks, particularly in flies that also experienced low developmental protein. These findings underscore the importance of assessing life history traits dynamically over time, as interactions between developmental and adult environments may drive complex, non-additive effects that are not apparent in cross-sectional measurements. Considering both additive and interactive effects in diverse genetic backgrounds will be critical for understanding the evolutionary and ecological consequences of nutritional variation.